გეორგიევსკის ტრაქტატის წინაპირობები – რუსეთის იმპერიის სტრატეგიული ინტერესები და საქართველო XVIII საუკუნის 70-იან წლებსა და 80-იანი წლების დასაწყისში - თაბუაშვილი, აპოლონ (My University, 2021)
In the early summer of 1782, the Russian imperial court decided to finally settle the issue of Crimea, Taman, and Kuban. The Russian government believed that the annexation of these territories would lead to war with the Ottomans. Therefore, active preparations for the impending war began. For the successful implementation of the developed plan, the relevant order of the emperor was issued and its implementation swiftly began. One of the most significant components of the plan was a stealth attack through the Caucasus. The Georgian kings were to help the Russian army through “sabotage” against the Ottomans. Without their participation in the war, it would have been almost impossible to successfully carry out the planned operation in the South Caucasus. Accordingly Correspondingly, according to the plan of Catherine II, a significant part of the mission was assigned to the Georgian kingdoms. The above circumstances prompted the Russian government to radically change its attitude towards Erekle II and Solomon I. For this very purpose, the Russian imperial court decided to raise the issue of patronage and began negotiations with the Georgian side.
PREREQUISITES FOR THE TREATY OF GEORGIEVSK – STRATEGIC INTERESTS OF THE RUSSIAN EMPIRE AND GEORGIA IN THE 1770S AND EARLY 80s
კონფერენცია მიძღვნილია აკადემიკოს კოტე წერეთლის 100 წლის იუბილესადმი/ DEDICATED TO THE 100TH ANNIVERSARY OF ACADEMICIAN KONSTANTINE TSERETELI
Keywords: კავკასიის კორპუსი; მფარველობა; ერეკლე II; ეკატერინე II; Caucasian Army Corps; Protectorate; Erekle II; Catherine II